Keeping Up-to-Date - Norman L Jones (Canadian Respiratory Journal)
As a senior (read older) practising respirologist, I have come to appreciate my position as editor, which keeps me current with present practice standards. Everyone talks about the volume and flow of new knowledge, and not a week goes by in which I feel that I know enough to treat my patients optimally. This is particularly the case when it comes to antibiotic usage: the number of antibiotics and the confident way that junior colleagues bandy them about leaves me distinctly depressed because most of the names mean little to me; even the families and generations of antibiotics seem beyond my grasp. That is why I welcomed the request from Dr Lionel Mandell to publish a summary statement on the use of antibiotics in community-acquired pneumonia (CAP), which appears on pages 371-382 of the current issue of the Canadian Respiratory Journal.